Prospective Evaluation of Short and Mid-Term Outcomes of Total Hip Arthroplasty Using the Accolade™ Stem. Issue 5 (September 2015) - Pierce, Todd P.; Jauregui, Julio J.; Cherian, Jeffrey J.; Elmallah, Randa D.K.; Robinson, Kristin; Mont, Michael A.
Purpose: Cementless press-fit total hip arthroplasty (THA) with the Accolade stem (Stryker Accolade™ TMZF, Mahwah, New Jersey) has demonstrated variable implant survivorship and outcomes. The purpose of this study was to analyse the: 1) implant survivorship; 2) complications; 3) functional outcomes; 4) overall quality of life; and 5) patient expectations and satisfaction following THA with this particular press-fit stem. Methods: A prospectively collected database of 222 patients who underwent THA at 7 institutions between 2006 and 2009 using the Accolade stem (Stryker Inc. Mahwah, New Jersey) was evaluated. Harris Hip Score (HHS) and SF-12 were used to assess the outcomes at 2- and 5-year follow-up. Kaplan-Meier survivorship was calculated at 5 years of follow-up. Results: The 5-year aseptic and all-cause survivorship rates were 99.4% (95% CI, 96.3 to 99.9%) and 97.9% (95% CI, 94.6 to 99.2%), respectively. At 2 and 5 years postoperatively, the patients demonstrated a mean HHS of approximately 89 points and 92 points, respectively. The mental and physical components of the SF-12 mean score increased with the physical component having a more marked increase. The mental and physical components of the SF-12 score increased to a mean of 46 and 45 points at 2 and 5 years, respectively. At 2-year follow-up, over 90% of patients were satisfied with their outcome in a majority of areas surveyed. Discussion: Our results suggest that the use of this press-fit construct results in tremendous improvements in functional and quality of life outcomes, along with excellent survivorship at short- and mid-term follow-up.